Do depicted suggestions of portion size on‐pack impact how much (un)healthy food children consume. (3rd January 2019) - Aerts, Goele; Smits, Tim
Abstract: In previous decades, portion and pack sizes of many foods tended to increase while, more recently, some foods started to downsize. These changes in actual portion sizes typically get coverage but less attention is given to the suggested portion sizes for multi‐serving food packages, and to what the impact is of the depicted portion sizes on‐pack. Using two studies with a mixed experimental design among young children, this paper examines the effects of depicted suggestions of portion size manipulation (regular vs. large—'large' corresponds to how brands typically depict portions). Both studies used a 2 × 2 × 2 crossover design, with the suggested portion size and food type as within‐ and order as between‐subjects manipulation. In Study 1, we used snacks (grapes and chocolate nuts). In Study 2, we compared two bread spreads (chocolate and cheese). In both the studies, we found that children ate more when presented with the larger depiction of the suggested portion size compared to the regular one. In Study 1, however, we found that children consumed more calories from the chocolate nut than the grape snack, while children did eat more grams of this healthier grape snack. We also showed that consumption in grams only differed between portion sizes when given grapes, which might be due to a possible ceiling effect of chocolate nut consumption. In Study 2, we also found a main effect for spread type as children ate more of chocolate compared to cheese spread. Our results indicate that this subtle on‐pack cue is persuasive. Moreover, policy makers and also marketers could use these insights to stimulate healthy eating in children.